THE EFFECTIVENESS OF GAMASLICE LEARNING MEDIA IN ENHANCING JOYFUL LEARNING - Kusuma, Anton Adi Suryo (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Fraction learning in elementary schools is often perceived as difficult and less engaging for students, which has an impact on low learning outcomes and motivation. This study aimed to examine the effectiveness of Gamaslice learning media, based on Javanese Gamelan, in enhancing joyful learning in mathematics instruction on fraction topics. The study employed a quasi-experimental method with a non-equivalent control group design, involving 60 fourth-grade students divided into an experimental class (using Gamaslice) and a control class (conventional learning). Data were collected through pretests and posttests and analyzed using the Kolmogorov–Smirnov normality test, Levene’s Test for homogeneity, independent samples t-test, and N-Gain analysis with the assistance of SPSS 23. The results indicated a significant difference (Sig. < 0.05) between the experimental and control classes, demonstrating that Gamaslice media was effective in improving students’ joyful learning. The N-Gain analysis showed that the control class was in the low category (-0.0017), while the experimental class exhibited a higher level of improvement. The integration of the Culturally Responsive Teaching (CRT) approach with game-based learning in Gamaslice created contextual, meaningful, and enjoyable learning experiences for elementary school students.